Collections of editorial cartoons by the trade union press: visual sources for a history against the grain (Tempo e Argumento, 2016)
The history of Brazil may be presented or interpreted with the aid of various historical sources. Among these sources, communicative production has generally gained increasing importance to the historiography making. Thus, we highlight the editorial cartoons in the context of the Brazilian trade union press, which, in our studies, occupy a central position as a communication product and historical source. Since the late 1970s, with the resurgence of the trade union movement under the aegis of a ‘new trade unionism,’ the editorial cartoon has been used as a significant communication strategy that reveals the broadest and most notorious political processes. Compiling sets of editorial cartoons into collections has helped providing a rich research material, promoting the availability of alternative historical sources for historiography making. This article aims to identify and analyze collections of editorial cartoons produced in the context of trade union press, characterizing them as historical sources to produce an analysis of history against the grain. Keywords: Editorial Cartoon; Trade Union Press; Historical Source; Visual Source; Communication Strategy.